Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010 Third International Workshop on Managing Requirements Knowledge 2010
DOI: 10.1109/mark.2010.5623812
|View full text |Cite
|
Sign up to set email alerts
|

Rationale management challenges in requirements engineering

Abstract: Abstract-Rationale and rationale management have been playing an increasingly prominent role in software system development mainly due to the knowledge demand during system evaluation, maintenance, and evolution, especially for large and complex systems. The rationale management for requirements engineering, as a commencing and critical phase in software development life cycle, is still under-exploited. In this paper, we first survey briefly the state-of-the-art on rationale employment and applications in requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Zahra et al conducted a requirements engineering visualization literature review and found that requirements evolution is having the least visualization support [13]. Requirement management tools support visualization of requirements however the important limitation is that these visualizations do not show the relationship between requirements [14].…”
Section: Challenges In Traceability Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Zahra et al conducted a requirements engineering visualization literature review and found that requirements evolution is having the least visualization support [13]. Requirement management tools support visualization of requirements however the important limitation is that these visualizations do not show the relationship between requirements [14].…”
Section: Challenges In Traceability Managementmentioning
confidence: 99%
“…The visualization of such evolving requirements and their relationships were also not considered by researchers who focussed on visualizing trace links [14,17,18].…”
Section: Challenges In Traceability Managementmentioning
confidence: 99%
“…Requirements rationale knowledge management is beneficial but also costly, and considerable resources, time, and effort are required before benefits [17]. However, in other side capturing tacit knowledge in the form of a requirements rationale is expected to be useful in many cases, such as providing greater help in understanding the complexity of the software application, for maintenance, for future evolution of the software, to assess changes and to predict possible changes [13], [18]- [20].People who involved in maintenance or change requirements activities can use the documentation produced by the rationale model to avoid spending time reconsidering decisions that have been previously considered [21].Furthermore, a rationale can help in reuse when similar issues occur and aids in the next project succeed [17]. Rationale reuse improves, reducing effort and decision time by avoiding several repetitive tasks [20].…”
Section: Introductionmentioning
confidence: 99%